Geovisualization tools to inform the management of vessel noise in support of species' conservation. (1st March 2019) - Cominelli, Simone; Leahy, Michael; Devillers, Rodolphe; Hall, G. Brent
Abstract: The growth of global ocean noise recorded over the past decades is increasingly affecting marine species and requires assessment on the part of marine managers. We present a framework for the analysis of species' exposure to noise from shipping. Integrated into a set of geovisualization tools, our approach focuses on exposure hotspot mapping, on the computation of probabilistic levels of exposure, and on the identification of shipping routes that minimize exposure levels for Cetacean species. The framework was applied to estimate noise exposure for the Southern Resident Killer Whale (SRKW) population, and for the exploration of possible ship traffic displacement scenarios in the Salish Sea, British Columbia. Four noise exposure hotspots were identified within the SRKW's core habitat. Exposure over these areas was mainly produced by six vessel classes, namely Ferries, Tugboats, Recreational Vessels, Vehicle Carriers, Containers, and Bulkers. Exposure levels showed variability across hotspots suggesting that a fine-scale spatial dimension should be included in the design of noise pollution mitigation strategies for the Salish Sea. The scenarios suggest that small changes in the current shipping lanes (3.4% increase in traveled distance) can lead to a 56% reduction of the overlap between vessel traffic and sensitive areas for SRKW. Graphical abstract: Image 1 Highlights: New geospatial methods and tools supporting the management of ocean noise. Hotspot mapping helps identify key noise exposure areas. Cumulative distribution functions allow identifying high-exposure vessel classes within a hotspot. Approach tested for southern resident killer whales in the Salish Sea, Canada. Method can help reduce the overlap between vessel noise and species core areas.